A mixed methods study of patient–provider communication about opioid analgesics. Issue 4 (April 2015) - Hughes, Helen Kinsman; Korthuis, Philip Todd; Saha, Somnath; Eggly, Susan; Sharp, Victoria; Cohn, Jonathan; Moore, Richard; Beach, Mary Catherine
Highlights Pain management discussions are common in outpatient HIV encounters. Providers may regard patients less favorably if opioids are discussed. These conversations were sometimes adversarial. Empathy may facilitate more productive discussions.